Understanding How Youth Navigate Political Information - Koren, Nitzan (Proceedings of the ALISE Annual Conference, 2023)
This work explores how we can design a Political Information Literacy (PIL) learning experience in out-of-school contexts. In collaboration with youth development and library educators and youth from historically marginalized communities, including 1.5- and second-generation immigrants, we ran participatory design sessions to identify how youth engage and make sense of political information while socially engaging and discussing misinformation, disinformation, and fake news. Preliminary findings show that youth are interested in creating positive, fun, and engaging experiences around political information and are interested in simplifying the idea of Political Information Literacy and related concepts, making sense of the connection of this concept to their lives, and making stronger connections between politics and their lives. Youth also identified a broad range of challenges, such as what they claimed to be inaccessible content, feeling insecure about their skills, experiencing information overload, and being concerned with their mental health. Youth also reported that they feel like they cannot trust what most consider reliable sources of information, as they perceive these channels as equally biased and promoting political agendas. Finally, youth were flexible thinkers, committed to listening, and respectful toward a broad range of ideas and perspectives (even when different than their own), positioning them as assets to their communities, especially around civic engagement efforts. This project continues collaborating with community partners, libraries, and immigrant youth to acquire PIL and engage in civic life.